The ESP enigma : the scientific case for psychic phenomena - Powell, Diane Hennacy (New York : Walker, 2009)
Integrating concepts from physics, neuroscience, and other disciplines, Dr. Powell offers an insightful and intriguing explanation of ESP, provocatively claiming that the existence of psychic abilities expands the understanding and appreciation of consciousness.
Integrating concepts from physics, neuroscience, and other disciplines, Dr. Powell offers an insightful and intriguing explanation of ESP, provocatively claiming that the existence of psychic abilities expands the understanding and appreciation of consciousness.
Includes bibliographical references (p. [232]-266) and index.
Keywords: Consciousness; Parapsychology